De novo microduplications at 1q41, 2q37.3, and 8q24.3 in patients with VATER/VACTERL association - Hilger, Alina Christine; Schramm, Charlotte; Pennimpede, Tracie; Wittler, Lars; Dworschak, Gabriel C.; Bartels, Enrika; Engels, Hartmut; Zink, Alexander M.; Degenhardt, Franziska; Müller, Annette M.; Schmiedeke, Eberhard; Grasshoff-Derr, Sabine; et al. (European journal of human genetics, 2013)
The acronym VATER/VACTERL association describes the combination of at least three of the following congenital anomalies: vertebral defects (V), anorectal malformations (A), cardiac defects (C), tracheoesophageal fistula with or without esophageal atresia (TE), renal malformations (R), and limb defects (L). We aimed to identify highly penetrant de novo copy number variations (CNVs) that contribute to VATER/VACTERL association. Array-based molecular karyotyping was performed in a cohort of 41 patients with VATER/VACTERL association and 6 patients with VATER/VACTERL-like phenotype including all of the patients’ parents. Three de novo CNVs were identified involving chromosomal regions 1q41, 2q37.3, and 8q24.3 comprising one (SPATA17), two (CAPN10, GPR35), and three (EPPK1, PLEC, PARP10) genes, respectively. Pre-existing data from the literature prompted us to choose GPR35 and EPPK1 for mouse expression studies. Based on these studies, we prioritized GPR35 for sequencing analysis in an extended cohort of 192 patients with VATER/VACTERL association and VATER/VACTERL-like phenotype. Although no disease-causing mutation was identified, our mouse expression studies suggest GPR35 to be involved in the development of the VATER/VACTERL phenotype. Follow-up of GPR35 and the other genes comprising the identified duplications is warranted.
Gesehen am 10.05.2021